'Conflict with the Law': Regulation & Homeless Youth Trajectories toward Stability. Issue 3 (20th December 2016) - Quirouette, Marianne; Frederick, Tyler; Hughes, Jean; Karabanow, Jeff; Kidd, Sean
Abstract: Youth without housing experience more regulation and conflict with criminal justice than their housed counterparts. Using in-depth qualitative interviews with fifty-one young people, we focus on how efforts to move away from homelessness towards long-term housing stability are impacted by conflict with law, a term referring to a broad range of experiences with various authorities in the legal system, social services, shelters, etc. Our paper comes out of a yearlong longitudinal study of the factors and processes affecting the transition away from youth homelessness in Toronto and Halifax. We consider practical barriers generated by conflict with law, but also the role that it can play in shaping the identity processes at the heart of successful transitions. Our findings highlight how conflict with law and regulation—even occurring before and during homelessness—has serious repercussions for young people well after they have left the streets. Résumé: Les jeunes sans domicile fixe se buttent à davantage de réglementation et de conflits avec l'appareil de justice criminelle que leurs pairs domiciliés. À l'aide d'entrevues qualitatives approfondies effectuées auprès de cinquante-et-un jeunes, nous étudions comment les efforts des jeunes pour effectuer la transition de l'itinérance à un logement stable sont frustrés par des conflits avec la loi, dans leur sens le plus large et incluant une grande variété d'expériences avec divers paliers de l'appareil de justice, des services sociaux, des refuges, etc. Notre analyse est le résultat d'un an d'étude longitudinale des facteurs et processus touchant les efforts des jeunes pour abandonner l'itinérance à Toronto et à Halifax. Nous examinons non seulement les obstacles concrets à l'atteinte d'un logement stable que produisent les conflits avec la loi, mais aussi le rôle que ces conflits jouent dans le façonnement de l'idée de soi des jeunes, facteur déterminant d'une transition réussie. Nos conclusions démontrent comment les conflits avec la loi et la réglementation – même ceux antérieurs à l'itinérance – ont de profondes répercussions sur les jeunes longtemps après leur expérience d'itinérance.